Implementasi Laporan Keuangan Syariah pada UMKM Kota Jambi: Analisis Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, dan Skala Usaha - Baitul Hasanah; Hasanah, Baitul; Mubyarto, Novy; Martaliah, Nur Fitri (Program Studi Manajemen Keuangan Syariah, 2025)
This study aims to determine the effect of education level, accounting understanding, and business scale on the implementation of sharia financial reporting in micro, small and medium enterprises in Jambi City. The population in this study were MSME actors in the culinary field in Jambi City in 2023 with the number of MSMEs in 11 sub-districts being 18.876 people who had been registered at the Jambi City Manpower, Cooperatives and MSMEs Office. population used using the Slovin approach formula. The sampling technique uses the random sampling method as a sampling technique. The data collection technique is using a questionnaire. Data uses the Statistical Package for Social Sciences (SPSS) 27 software. Based on the results of the data analysis carried out by this researcher, it shows that the influence of education level has a significant effect on the implementation of sharia financial reporting. Accounting understanding has a significant effect on the implementation of sharia financial reporting. Business scale does not affect the implementation of sharia financial reporting. Education level, accounting understanding, and business scale affect the implementation of sharia financial reporting.